Evaluation of the Application for new alternative biodiesel production process for rendered fat of Cat 1 (BDI‐RepCat process, AT). (14th November 2017) - ,; Ricci, Antonia; Allende, Ana; Bolton, Declan; Chemaly, Marianne; Davies, Robert; Girones, Rosina; Herman, Lieve; Koutsoumanis, Konstantinos; Lindqvist, Roland; Nørrung, Birgit; Robertson, Lucy; et al.
Abstract: A new alternative method for the production of biodiesel from rendered fat of all categories of animal by‐products was assessed. The process was compared to the approved biodiesel production process described in Chapter IV Section 2 D of Annex IV of Commission Regulation (EU) 142/2011. Tallow derived from Category 1 material is treated according to Method 1 from the same Regulation (133°C, 20 min, 3 bar) and subsequently mixed with 15% methanol, heated to reaction temperature (220°C) in several heat exchangers and transferred into the continuous conversion reactor by means of a high pressure pump (80 bar) for 30 min. In the conversion phase, there is an exposure to methanol in the absence of alkaline or acidic conditions. The impact of this procedure on the thermostability of transmissible spongiform encephalopathy (TSE) has not been assessed in the literature. After the reaction, the biodiesel/glycerol mixture is distilled under vacuum at a minimum temperature of 150°C and a maximum pressure of 10 mbar, which is equivalent to the distillation step in the approved biodiesel production process, for which a 3 log10 reduction factor in PrP27–30 was obtained. Therefore, a similar level of TSE infectivity reduction could be expected for that phase of the method. A previous EFSA Opinion established that a reduction of 6 log10 in TSE infectivity should be achieved by any proposed alternative method in order to be equivalent to the approved processing method. This level of reduction has not been shown with experimental trials run under conditions equivalent to the ones described for the RepCat process. It was not possible to conclude whether or not the level of TSE infectivity reduction in the RepCat process is at least of 6 log10 . Therefore, it was also not possible to conclude about the equivalence with the approved biodiesel production process.